ACTIONABLE STATEMENTS IN GUIDELINES - Lotfi, Tamara (My University, 2025)
Guidelines are systematically developed to assist their users in making decisions. They are presented as documents or online reports that contain a set of actionable statements and should be created following a rigorous and inclusive process. Lengthy guidelines without clear labeling of actionable statements and explicit rationales for judgments can mislead physicians. Previous work has described and tested two main types of actionable statements: formal recommendations (i.e., actionable statements that are evidence-based and have a clear direction for or against an intervention), and good practice statements (i.e., necessary actionable statements that do not require a thorough search for the evidence and that ensure larger net desirable consequences when issuing them). This thesis focuses on a framework helping to identify the different types of actionable statements that are included in guidelines, understanding the relationship between guideline characteristics and the type of actionable statements, as well as exploring guideline developers’ perceptions of creating rigorous actionable statements using the framework. The framework characterizes five types of actionable statements: formal recommendations, research only recommendations, good practice statements, informal recommendations, and implementation considerations, tools and tips. We define each of these types and provide a description of what they are and what they are not. Given the risk that is associated with giving wrong advice, we specifically focus on informal recommendations where the risk is highest. Informal recommendations are not based on a rigorous process, because they are, by definition, not based on systematic reviews of the evidence when they should be. Our findings suggest that the implementation or development of informal recommendations should be discouraged. In this thesis, we also explore the perceptions of guideline developers towards using the framework. Through a qualitative study design, we were able to gather input from guideline developers and members of guideline developing organizations on how to enhance its use for the guideline development stage.